Risk factors of thrombocytopenia among pregnant women attending antenatal clinic at Parirenyatwa Group of Hospitals, 2023 – 2024 - Chamunorwa Chikwengo, Ronald; Ifeanyi Obeagu, Emmanuel; Salissou, Maibouge Tanko Mahamane (Ananda - Health & Education Foundation, 2025)
Background: Thrombocytopenia is a common hematological finding during pregnancy, affecting approximately 7-12% of pregnancies globally. The prevalence of thrombocytopenia among pregnant women in Africa is around 10.23%. Specific data might be less readily available in Zimbabwe hence the present study Objective:This study aimed to determine the prevalence of thrombocytopenia and identify associated risk factors among pregnant women attending antenatal clinics at Parirenyatwa Group of Hospitals(PGH) Method: The study used an analytical cross sectional design conducted at the PGH Haematology Laboratory. Using purposive sampling we enrolled all pregnant women over 18 years of age receiving ANC at PGH, from June 2023 to June 2024 at PGH. Chi square test was used to test association between thrombocytopenia and various risk factor P < 0.05 was set as statistically significant Results: A total of 380 pregnant women were enrolled in this study. The prevalence of thrombocytopenia was 18.7%. Pregnant women In their majority were located in urban high-density areas (45%) and were young (18–25 years: 31% of cases). With regard to the disease severity the severe thrombocytopenia peaked in the third trimester (55%), correlating with hypertensive disorders. Hypertension (OR=2.51, 95% CI=1.25–5.03, p=0.024) and iron deficiency anaemia (IDA); OR=1.81, 95% CI=1.01–3.26, p=0.042) were significant predictors as well as age being lesser than 30 years old OR 0.27 CI (0.14-0.5), p=0.0001) but gestational diabetes mellitus (GDM) showed no association (OR=0.96, p=0.939) Conclusion: Thrombocytopenia is a significant concern in pregnancy, particularly in early gestation, with mild cases dominating. IDA and high-density residency emerged as critical risk factors, while hematological biomarkers demonstrated predictive utility.